2021
DOI: 10.3390/ijms22179345
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Analysis of Proteome Dynamics during Bacillus subtilis Sporulation

Abstract: Bacillus subtilis vegetative cells switch to sporulation upon nutrient limitation. To investigate the proteome dynamics during sporulation, high-resolution time-lapse proteomics was performed in a cell population that was induced to sporulate synchronously. Here, we are the first to comprehensively investigate the changeover of sporulation regulatory proteins, coat proteins, and other proteins involved in sporulation and spore biogenesis. Protein co-expression analysis revealed four co-expressed modules (terme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…The sporulation frequencies were significantly reduced when compared to wild-type in the sspA and sspB strains, with the most extreme phenotype observed for the sspA deletion (33-fold reduction, p -value < 0.0001, Figure 1C and Supplementary Table 2 ). The SASPs are synthesized and accumulate after the engulfment of the spore occurs ( Tu et al, 2021 ), so they are not involved in the early sporulation process. The SASPs play a role in spore heat resistance [see below, ( Setlow, 2006 )], and heat treatment is used during the determination of sporulation frequency, which could partially explain the observed phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The sporulation frequencies were significantly reduced when compared to wild-type in the sspA and sspB strains, with the most extreme phenotype observed for the sspA deletion (33-fold reduction, p -value < 0.0001, Figure 1C and Supplementary Table 2 ). The SASPs are synthesized and accumulate after the engulfment of the spore occurs ( Tu et al, 2021 ), so they are not involved in the early sporulation process. The SASPs play a role in spore heat resistance [see below, ( Setlow, 2006 )], and heat treatment is used during the determination of sporulation frequency, which could partially explain the observed phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis was performed as described in Tu et al (2021). Raw MS/MS data were searched in Maxquant (version: 1.6.14.0) (Cox and Mann, 2008) against an in house created B. tabaci proteome database and a S. lycopersicum database downloaded from Uniprot (06/2020).…”
Section: Phloem Exudate Collectionmentioning
confidence: 99%
“…With the increasing demand for in-depth knowledge of the molecular physiology of spore-forming bacteria, further elucidation of the biological processes at hand is needed to completely comprehend the metabolic and adaptive networks operating within Bacillus cells and spores. This is also why the global analysis of proteins by proteomics is increasingly used in the sphere of research of bacterial sporulation, germination and outgrowth (4)(5)(6). Even though B. subtilis, a well-studied model of gram-positive bacteria, was among the first to have its entire genome sequenced, only around 50% of its theoretical proteome is routinely measured in proteomics studies while up to 80% has been identified when aggregating data from a large number of studies (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins are of particular importance as some, such as small acid soluble proteins (SASPS) and highly cross-linked coat proteins, play a crucial role in spore resilience and structure (9,10). Because of this central role of proteins in the physical attributes of spores and concomitantly their resistance properties (11), analysis of protein content, quantity, crosslinking and complex formation and coat proteins using proteomics has been of the highest interest and multiple studies have been done over the past two decades (4)(5)(6)(12)(13)(14)(15)(16). Spore analysis through proteomics has multiple factors related to sample preparations that can influence the sensitivity, completeness and fidelity of the spore proteome: i) spore sample purity, ii) spore lysis efficiency, iii) protein extraction and solubilization efficiency and iv) completeness of protein digestion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation